The Arguments of Radical Atheism – Some Critical Reflections. Issue 2 (November 2019) - Elgat, Guy
Abstract : The paper provides a critical review of Martin Hägglund's influential Radical Atheism . The paper focuses on what Hägglund calls 'radical atheism': the view that according to Derrida 'the best is the worst'. First, the paper critically examines Hägglund's reconstruction of Derrida's argument for the structure of the trace or 'the spacing of time'. This analysis clarifies one of the central premises in Hägglund's argument for radical atheism: the 'contamination' claim, according to which anything temporal is open as such to the future and is thus alterable in some way. The paper then turns to highlight some of Hägglund's rhetorical slippages that seem to be supported by the contamination claim but actually move beyond what it licenses. Next, the paper focuses critically on the argument for radical atheism and shows how it relies on an unwarranted premise that lies hidden in the discussion of the structure of the trace. Finally, the second central argument that informs Hägglund's work is questioned, that is, the argument for the view that what we are always and already committed to is to live on, that is, survive, so that it is this desire for the mortal that lies behind all our desires.